Trends, predictors, and outcomes of transcatheter aortic valve implantation in patients with bicuspid aortic valve related disease: Insights from the Nationwide Inpatient Sample and Nationwide Readmission Database. Issue 6 (2nd October 2022) - Ullah, Waqas; Zahid, Salman; Muhammadzai, Hamza; Khalil, Fouad; Kumar, Arnav; Minhas, Abdul Mannan Khan; Khan, Muhammad Zia; Virani, Salim S.; Fischman, David L.; Shah, Pinak; Bhatt, Deepak L.
Abstract: Background: Transcatheter aortic valve implantation (TAVI) has increasingly been utilized in patients with bicuspid aortic valve (BAV) related aortic stenosis (AS) with insufficient large‐scale data on its safety. Methods: The Nationwide Inpatient Sample and Nationwide Readmission Database (2011–2018) were queried to identify patients undergoing TAVI for BAV versus trileaflet aortic valve (TAV) associated AS. The in‐hospital, 30‐ and 180‐day odds of outcomes were assessed using a propensity‐matched analysis (PSM) to calculate adjusted odds ratios (aOR) with its 95% confidence interval (CI). Results: A total of 216, 723 TAVI (TAV: 214, 050 and BAV: 2, 673) crude and 5, 347 matched population (TAV: 2, 674 and BAV: 2, 673) was included in the final analysis. At index admission, the adjusted odds of in‐hospital mortality (aOR: 1.57, 95% CI: 0.67–3.66), stroke (aOR: 0.77, 95% CI: 0.38–1.57), cardiac tamponade (aOR: 0.75, 95% CI: 0.17–3.36), vascular complications (aOR: 0.33, 95% CI: 0.09–1.22), cardiogenic shock (aOR: 1.77, 95% CI: 0.93–3.38), paravalvular leak (aOR: 0.55, 95% CI: 0.26–1.14), need for mechanical circulatory support device, and permanent pacemaker implantation (PPM) (aOR: 1.02, 95% CI: 0.69–1.52) were not significantly different between TAVI for BAV versus TAV. At 30‐ and 180‐day follow‐up duration, the risk of stroke and major postprocedural complications remained similar, except that TAVI in BAV had a higher incidence of PPM implantation compared with TAV. The yearly trend showed an increase in the utilization of TAVI for both TAV and BAV and a steady decline in the overall annual rate of in‐hospital complications. Conclusion: TAVI utilization in patients with BAV has increased over the recent years. The relative odds of in‐hospital mortality, and all other major complications, were similar between patients undergoing TAVI for BAV‐ and TAV‐related AS.